Minimal intervention dentistry for partially dentate older adults. (1st February 2019) - Allen, Patrick Finbarr; Da Mata, Cristiane; Hayes, Martina
Abstract : Background: Chronic dental and oral diseases, such as dental caries and periodontal disease, continue to be a significant health problem among older adults. Given the rapidly changing profile of the ageing population, and their complex health needs, there is a need to develop new evidence‐based approaches to oral health care. Recently, care philosophies have been developed that take a minimally invasive, functionally oriented, approach to oral health care with a focus on providing a reduced, but healthy, natural dentition which can be maintained with support of better oral hygiene. Method: A review of the literature concerning use of minimal intervention dentistry (MID) to manage caries and toothloss in partially dentate older adults was undertaken. Results: A variety of chemotherapeutic agents are available to prevent development of root caries and/or arrest root caries lesions, with professionally applied solutions (ie 22 500 NaF, 38% SDF or 40% CHX) every 3 to 6 months demonstrating best outcomes. Application of 38% SDF annually in high‐risk, institutionalised older adults is effective in arresting root caries. Atraumatic restorative treatment can be used successfully to manage active carious lesions and limit the removal of natural tooth tissue. Finally, functionally oriented treatment planning to manage partial toothloss is successful in terms of quality of life impact and cost‐effectiveness. Conclusion: Available evidence is somewhat limited and more long‐term studies are need. However, currently available evidence suggests that minimal intervention dentistry can be predictable and cost‐effective in older adults.